“Sailing Beyond Limit” sebagai Analogi Latihan Keterampilan Manajemen Mahasiswa dalam Upaya Implementasi Peran Agent of Change - Trisnapradika, Gustina Alfa; Juhara, Kanahaya Putri; Bahri, Alfino Kautsar; Ananta, Putri Rossa; Siregar, Nadia Itona; Ningrum, Novita Kurnia (Bumi: Jurnal Hasil Kegiatan Sosialisasi Pengabdian kepada Masyarakat, 2026)
Students have a strategic role as agents of change that requires adequate leadership and managerial skills. Formal learning in the classroom has not been able to fully develop these practical skills. This community service activity aims to improve the basic management skills of students at the Faculty of Computer Science, Universitas Dian Nuswantoro through Basic Student Management Skills Training (LKMM TD) with the theme Sailing Beyond Limits. The implementation method uses a Participatory Learning Action approach that includes problem identification, strategic planning, activity implementation, and joint evaluation. The activity was attended by 193 students from student organizations and general students. The learning process was carried out through lectures, case studies, discussions, group work, and pre- and post-tests. The evaluation results showed a significant increase in participant capacity, marked by an increase in the average score from 68.21 percent in the pre-test to 91.69 percent. LKMM TD activities effectively equip students with managerial, leadership, communication, and motivational control skills as provisions for carrying out the role of student agents of change.